origem e distribuição do nervo toracodorsal em fetos de suínos da linhagem Pen Ar Lan - Tavares, Eleusa Marta Mendonça (2011)
Considering the importance of the nerves that make up the brachial plexus was aimed to study the origin and distribution of the thoracodorsal nerve. Thus were used 30 pig fetuses of lineage Pen Ar Lan obtained from miscarriages in farms of the Triangulo Mineiro region. The specimens were prepared by injection of solutions of Neoprene Latex "450" at 50% and 10% formaldehyde in the aorta, and immersion in the same solution for a minimum of 48 hours. The dissections were performed bilaterally up to reach the brachial plexus that has emerged from the spinal ventral branches of the sixth (C6), seventh (C7) and eighth (C8) cervical nerves and of the first thoracic (T1). It was found that the thoracodorsal nerve was formed from C8 in two sides (3.33%), T1 in 17 sides (28.33%), and C8 and T1 in 41 sides (68.33) and that there was symmetry in terms of its origin, in 23 animals (76, 66%). It was found that the thoracodorsal nerve sent branches in 100% of cases for the latissimus dorsi muscle, and 36.66% for the teres major.